Price distributions and competition - Kenneth Burdett; Eric Smith (Federal Reserve Bank of Atlanta, 2009)
Considerable evidence demonstrates that significant dispersion exists in the prices charged for seemingly homogeneous goods. This paper adopts a simple, flexible equilibrium model of search to investigate the way the market structure influences price dispersion. Using the noisy search approach, the paper demonstrates the effects of having a single large, price-leading firm with multiple outlets and a competitive fringe of small firms with one retail outlet each.
Keywords: D40; L7; 330; price dispersion; consumer search; market structure